Orientalist Approaches to the Origins of Yezidi Beliefs in the Context of Abrahamic Religions - Birlik, Rezan (Ahmet İshak DEMİR, 2025)
Mesopotamia has long possessed a cosmopolitan structure that has served as a homeland for numerous religions, belief systems, and cultures. The ?Adawiyya order emerged as a Sufi tradition that spread throughout this region in the twelfth century. Its founder, Shaykh ?Ad?, was subsequently portrayed by his followers as a supra-human figure through excessive veneration. Yezidism, influenced by neighboring religions and belief systems, emerged within a relatively short period as a transformation deriving from the ?Adawiyya tradition. Due to its syncretic character, Yezidism attracted the attention of Orientalist scholars, who examined the tradition and introduced it to the Western world, where it generated considerable interest. However, Orientalist perspectives, shaped by the closed nature of Yezidi society and philosophical interpretations detached from historical realities, contributed to the emergence of a contradictory portrayal of Yezidism. As one of the research subjects within the field of the history of Islamic sects, Yezidi doctrine contains discernible elements derived from Judaism, Christianity, and Islam. Studies conducted by Orientalist scholars on these established traditions led to the formulation of diverse theories concerning the origins of Yezidism. Based on their observations and analyses, each researcher tended to trace the religious foundations of Yezidi belief back to the Abrahamic religions. While some scholars have argued that Yezidism is rooted in a specific religion or belief system in terms of doctrine, ritual practice, and ethnic context, others have maintained that it represents an eclectic structure formed through the synthesis of traditions from various religions and belief systems. The influence of the Abrahamic religions on Yezidi religious traditions is underpinned by certain political and religious factors. Consequently, attitudes toward the Abrahamic faiths have constituted a significant element in the formation of Yezidi doctrine.

Mezopotamya, birçok din, inanç ve kültürün yuvalandığı kozmopolit bir yapıya sahiptir. Adeviyye tarikatı, 12. yüzyılda bu coğrafyada yayılım göstermiş tasavvufî bir ekol olarak kendini göstermiştir. Adeviyye’nin kurucusu Şeyh Adî, kendisinden sonraki takipçileri tarafından aşırı tazimle insanüstü bir varlık olarak gösterilmiştir. Yezîdîlik ise, komşu din ve inanışların etkisiyle de kısa sürede Adeviyye’den bir dönüşüm olarak ortaya çıkmıştır. Senkretik yapısı ile oryantalistlerin dikkatini çeken Yezîdîlik, oryantalistler tarafından incelenerek Batı dünyasına tanıtılmış ve ilgi uyandırmıştır. Ancak oryantalistlerin bakış açıları, Yezîdîliğin kapalı yapısı ve tarihsel gerçeklerden uzak felsefi yorumlar nedeniyle çelişkili bir portre oluşmasına neden olmuştur. İslâm mezhepleri tarihi biliminin araştırma konularından biri olan Yezîdî doktrini içerisinde; Yahudilik, Hristiyanlık ve İslâm dinlerine ait izler bulunmaktadır. Oryantalistlerin bu yerleşik gelenekler üzerinde yaptığı çalışmalar, Yezîdîliğin kökenlerine dair farklı teoriler ortaya koymalarına neden olmuştur. Her bir araştırmacı, yaptığı gözlem ve incelemeler neticesinde Yezîdîliğin inanç kökenlerini İbrahimî dinlere dayandırma eğiliminde olmuştur. Kimi araştırmacılar, Yezîdîliğin inanç, ritüel ve etnik bağlamda belirli bir din veya inanca dayandığını ileri sürerken, kimileri farklı din ve inançların gelenekleriyle harmanlandığı eklektik bir yapı olduğunu savunmuştur. İbrahimî dinlerin Yezîdî inanç gelenekleri üzerindeki tesirlerinin arka planında siyasî ve dinî bazı gerçekler yatmaktadır. Dolayısıyla Yezîdî doktrininin şekillenmesinde İbrahimî dinlere yönelik bakış açısı önemli bir unsur oluşturmuştur.
İbrahimî Dinler Bağlamında Yezîdîliğin İnanç Kökenleri Üzerine Oryantalist Yaklaşımlar
Keywords: History of İslamic sects; İslam Mezhepleri Tarihi